Digital Diplomacy and Africa Geopolitics in the Digital Age - Adepo, Temitope (Journal of Contemporary International Relations and Diplomacy, 2026)
African states are increasingly adopting digital diplomacy to enhance their global visibility and influence; however, existing scholarship offers only fragmented accounts of these efforts and does not adequately explain how Africa’s digital engagement contributes to its geopolitical positioning. This study addresses this gap by examining how African states and regional institutions deploy digital tools to shape diplomatic identities, articulate emerging digital norms, and negotiate influence within the evolving global digital order. Drawing on a qualitative research design, the study analyses policy documents, African Union frameworks, national cybersecurity and digital governance strategies, official social-media communications, and reports from international organisations. Empirical evidence reveals that Africa’s digital diplomacy is becoming increasingly structured and purposeful. The African Union’s use of virtual diplomatic platforms during the COVID-19 pandemic, Kenya’s development of a National Cybersecurity Strategy, and Nigeria’s expanded use of digital communication collectively demonstrate Africa’s efforts to project identity, assert digital sovereignty, and participate in global norm-setting. Findings further show that Africa faces significant challenges—including technological dependence, cybersecurity vulnerabilities, and internet shutdowns—that constrain its digital influence. Nonetheless, emerging opportunities exist, particularly in the creative economy and in continental initiatives aimed at harmonising digital governance. The study concludes that Afro-digital diplomacy is evolving into a strategic tool through which African states seek to enhance geopolitical relevance, challenge longstanding marginalisation, and shape global digital governance. It recommends strengthening indigenous digital infrastructure, enhancing cybersecurity cooperation, improving regional policy harmonisation, and expanding Africa’s presence in global digital policy forums to consolidate gains and advance the continent’s digital sovereignty.